ANALISIS FAKTOR INTERNAL PENYEBAB TERJADINYA PIUTANG TAK TERTAGIH - Fitri Dwi Ulma; Mumu Mohamad Fadjar; Tina Kartini (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2020)
This study aims to determine the internal factors that cause uncollectible receivables in the Koperasi Simpan Pinjam Warga Setia Sejahtera Cisaat.This research uses a descriptive method with a qualitative approach. The author uses data collection techniques by observation, interview and documentation. Data processing that is by means of descriptive analysis is a writing technique by describing all data obtained through interviews, library materials and documentation and then analyzing it with written source criteria. The results of this study indicate that reports of Savings and Credit Cooperatives of Setia Sejahtera Citizens in 2015-2019 continue to experience an increase. The internal factors that cause the occurrence of uncollectible receivables, namely the weak credit administration system, the weak credit supervision system, and collusion between creditors and debtors. Keywords: Internal Factors, Bad Debts.